2022
DOI: 10.1002/ccr3.6597
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune meningoencephalitis associated with anti‐glutamic acid decarboxylase antibody following COVID‐19 infection: A case report

Abstract: Anti‐glutamic acid decarboxylase (Anti‐GAD) are associated with various neurologic condition; but no meningitis has been reported with it, so far. Evidence demonstrates the associated of autoimmune meningoencephalitis with COVID‐19 infection. Here, we report a 44‐year‐old female with progressive loss of consciousness with anti‐GAD65 meningoencephalitis 1 month after COVID‐19 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…Moreover, GAD65 had the strongest binding capacity to HLA in this work, with two different combinations of mimicry. Cases of autoimmune encephalitis associated with GAD65 have been described following SARS-CoV-2 infection [15,68]. This finding reinforces the association of SARS-CoV-2 MM and the clinical findings related to anti-GAD65 antibody.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, GAD65 had the strongest binding capacity to HLA in this work, with two different combinations of mimicry. Cases of autoimmune encephalitis associated with GAD65 have been described following SARS-CoV-2 infection [15,68]. This finding reinforces the association of SARS-CoV-2 MM and the clinical findings related to anti-GAD65 antibody.…”
Section: Discussionsupporting
confidence: 71%
“…Numerous demyelinating disorders such as multiple sclerosis (MS), neuromyelitis optica spectrum diseases (NMOSDs), acute disseminated encephalomyelitis (ADEM), myelitis, and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) have been described as post and para-infectious complications of COVID-19 [6], with the most common forms of AE following SARS-CoV-2 infection being limbic encephalitis and Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis [14]. Important studies have identified the presence of autoantibodies anti-glutamic acid decarboxylase 65-kilodalton isoform (anti-GAD65) [15], anti-myelin oligodendrocyte glycoprotein (anti-MOG), and others [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A 44-year- old female patient has been reported under the diagnosis of “meningoencephalitis” associated with GAD65 Abs, 1 month after receiving remdesivir for COVID-19 infection ( Table 1 ). The CT scan showed hydrocephalus and some meningeal enhancement; however, it is unclear whether the findings were related to COVID-19 infection ( 17 ). On the other hand, Triplett and colleagues reported on a 21-year-old female patient with seizures and progressively decreased level of consciousness with MR showing leptomeningeal enhancement aside from prominent hyperintense lesions involving both frontal lobes ( 18 ).…”
Section: Discussionmentioning
confidence: 99%